Territorial Defense Management: An Effective Military Strategy in the Contemporary Era - Priyanto Priyanto; Mia Kusmiati (International Forum of Researchers and Lecturers, 2025)
Purpose –This article aims to examine Territorial Defense Management (TDM) as an adaptive defense strategy in the contemporary era, with a focus on the synergy of UAV–sensor fusion–C2 technologies, whole-of-defense cyber orchestration and strengthening community resilience in facing multidimensional threats. Design/methodology/approach –This study employed a Systematic Literature Review (SRB) approach, using scientific literature sources from 2021–2025 from Scopus, IEEE, Springer, ScienceDirect, Garuda, and ResearchGate. Thirty-one primary articles were selected through rigorous screening and then analyzed using thematic coding and data triangulation to ensure the validity of the findings. Findings –The study results show that: (1) UAVs with sensor fusion increase the effectiveness of regional surveillance, although they require a counter-UAV system and good spectrum governance; (2) whole-of-defense cyber is proven crucial with the support of threat intelligence, territorial cyber operations centers, and AI for anomaly detection and automated response; (3) community resilience strengthens defense through emergency communications, early warning systems, and community participation in joint training with authorities. Practical implications –The effectiveness of MPT can be enhanced through standardization of IoMT architecture across the military services, counter-UAV and cyber exercises at the regional level, and the development of quantitative metrics to measure community resilience linked to military-level readiness. Originality/value –This article contributes by integrating technology, cyber, and community perspectives into a single adaptive MPT framework, thereby strengthening deterrence, rapid response, and socio-technological resilience. This approach is relevant for strengthening Indonesia's modern defense doctrine.